Building solid waste regenerated composite roadbed filler and preparation method thereof

By mixing construction solid waste with mineral blends and using composite adhesives and nanomontmorillonite and other technologies, building solid waste recycled composite roadbed fillers with improved permeability and freezing resistance were prepared, which solved the problem of insufficient permeability and freezing resistance in highway construction and achieved high-quality regeneration and utilization of construction solid waste.

CN119569362AActive Publication Date: 2025-03-07ZHEJIANG COMM CONSTR GRP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510138020.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The prior art is difficult to provide construction solid waste recycled concrete with high permeability and freezing resistance in highway construction.

Method used

By mixing construction solid waste with mineral blends such as fly ash or slag powder in a specific proportion, and using composite adhesives and doped nanomontmorillonite, a construction solid waste regenerated composite roadbed filler with improved permeability and frost resistance is prepared.

Benefits of technology

It has achieved high-quality recycling and utilization of construction solid waste, improved the seepage and frost resistance of concrete, and solved the problem of shortage of sand and gravel materials in highway construction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of mortar concrete compositions, in particular to a building solid waste regenerated composite roadbed filler and a preparation method thereof. The building solid waste regenerated composite roadbed filler consists of building solid wastes and mineral admixtures, the mineral admixture is one or more of fly ash, silica fume, slag powder, limestone powder, phosphorus slag powder and zeolite powder. Compared with the prior art, the building solid waste regenerated composite roadbed filler has the advantages that the building solid waste and the mineral admixture are organically combined, the advantages of the building solid waste and the mineral admixture are exerted, and the problems of high-quality recycling of the solid waste and shortage of sandstone materials for highway construction are solved. The concrete can be applied to building solid waste full-recycled concrete prepared from prefabricated parts in expressway construction such as paving of conical slopes, arched frameworks and side ditches, and the anti-permeability and anti-freezing performance can be improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mortar concrete compositions, and in particular to a composite roadbed filler recycled from construction solid waste and a preparation method thereof. Background Art

[0002] CN115716729A discloses an industrial construction solid waste negative carbon roadbed filler and a preparation method thereof, including S1, using industrial solid waste to prepare negative carbon gel material, S2, using construction solid waste to regenerate negative carbon roadbed filler. The invention uses industrial solid waste and construction solid waste as main materials, realizes the comprehensive utilization of both resources, and the advantages of the two complement each other, which can alleviate the current problems of land occupation and environmental pollution caused by solid waste hoarding; using construction solid waste to regenerate negative carbon to reinforce coarse aggregate can reduce the dependence of engineering construction on natural sand and gravel; providing a new way to solve the current shortage of roadbed filler supply; the preparation process of negative carbon roadbed filler is simple, and it can be prepared on site or processed in factories around the city, with short transportation distance and low cost, which can effectively reduce the pressure of industrial construction solid waste disposal and improve disposal efficiency.

[0003] CN111393065A discloses a composite roadbed filler made of recycled construction solid waste and a preparation method thereof. The roadbed filler is composed of the following materials by mass percentage: 5-70% brick-concrete recycled aggregate, 5-75% mud cake filler, 1-10% slaked lime, 1-10% fly ash, 0.5-4% HEC, and 10-20% water. The composite roadbed filler made of recycled construction solid waste has high strength and small drying shrinkage, and realizes the resource utilization of construction solid waste such as discarded clay bricks, discarded concrete, and mud cakes, solves the pollution problem of landfill disposal of construction solid waste and the damage to the environment caused by mining of natural fillers, and alleviates the current situation of shortage of natural resources.

[0004] The solutions reported in the above patent documents do not solve the problems of anti-seepage and anti-freezing properties at the same time. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide fully recycled concrete made of construction solid waste that can be used in the preparation of prefabricated components in highway construction such as cone slopes, arched frames and ditch paving, which can simultaneously improve the anti-seepage and anti-freeze properties.

[0006] To achieve the above-mentioned purpose, the present invention provides a construction solid waste recycled composite roadbed filler and a preparation method thereof.

[0007] The construction solid waste recycled composite roadbed filler consists of construction solid waste and mineral admixtures.

[0008] The construction solid waste and the mineral admixture are mixed in a mass ratio of 6-8:2-4.

[0009] The mineral admixture is one or more of fly ash, silica ash, slag powder, limestone powder, phosphorus slag powder and zeolite powder.

[0010] The mineral admixture is a mixture of fly ash and slag powder.

[0011] The mineral admixture is a mixture of fly ash and slag powder in a mass ratio of 2-4:1-2.

[0012] The preparation method of the construction solid waste is as follows, in parts by weight:

[0013] (1) 80-120 parts of waste concrete are sent to a crusher for primary crushing, and then sent to a screening machine for screening to separate solid waste with large particle size and solid waste with small particle size;

[0014] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The secondary screened materials are sent to a washing machine for washing, and 40-110 parts of recycled coarse aggregate and 10-40 parts of recycled fine aggregate are obtained by wind classification;

[0015] (3) Mix 5-7 parts of tannic acid aqueous solution and 3-5 parts of gelatin aqueous solution, stir at 5000-6000 r / min for 20-40 minutes, dry, grind and sieve, and add to 4-6 parts of ethylene glycol aqueous solution for dilution to obtain a composite adhesive;

[0016] (4) Mix 8-12 parts of phase change wax and 4-6 parts of nano-montmorillonite, place under 80-90 kPa vacuum conditions and stir for 6-8 hours until adsorption is complete to obtain doped nano-montmorillonite;

[0017] (5) Add 50-70 parts of recycled coarse aggregate, 10-20 parts of composite adhesive, and 10-20 parts of doped nano-montmorillonite to 100-150 parts of water, stir at a speed of 2000-4000 r / min for 1-2 hours to allow the doped nano-montmorillonite to completely adhere to the surface of the recycled coarse aggregate for shaping, dry until the moisture content is less than 2.0wt%, and finally mix with recycled fine aggregate to obtain the construction solid waste.

[0018] In the step (1), the large particle size is 10-50 mm, and the small particle size is 1-10 mm.

[0019] In the step (1), the particle size of the recycled coarse aggregate is 5-30 mm, and the particle size of the recycled fine aggregate is 1-5 mm.

[0020] The tannic acid aqueous solution in step (3) is a 5-10 wt % tannic acid aqueous solution.

[0021] The gelatin aqueous solution in step (3) is a 4-6 wt % gelatin aqueous solution.

[0022] The ethylene glycol aqueous solution in step (3) is a 40-60wt% ethylene glycol aqueous solution.

[0023] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0024] The construction solid waste and mineral admixture are mixed to obtain the construction solid waste recycled composite roadbed filler.

[0025] The composite roadbed filler recycled from construction solid waste of the present invention organically combines two types of waste, construction solid waste and mineral admixture, to give full play to their respective advantages. The construction solid waste is obtained by crushing, screening, shaping, mixing and other processes using waste concrete as raw materials, and the mineral admixture refers to a powder material with one or more oxides such as silicon, aluminum, calcium as main components, with a specified fineness, which can be added to concrete to improve the performance of concrete. The composite mineral admixture in the composite roadbed filler recycled from construction solid waste of the present invention is one or more of fly ash, silica ash, slag powder, limestone powder, phosphorus slag powder and zeolite powder. Fly ash, as a mineral admixture, can be widely used in concrete. Fly ash is the powder collected from the flue gas of a pulverized coal furnace; silica ash is the dust discharged through the flue when smelting ferrosilicon alloy or industrial silicon. It is a powder material with amorphous silicon dioxide as the main component obtained by collecting; slag powder refers to the powder material that is obtained by drying and grinding granulated blast furnace slag to a considerable fineness and meeting the corresponding activity index. Its activity is higher than that of fly ash; limestone powder is a powder material that is made from limestone of a certain purity and is ground to a specified fineness; phosphorus slag powder is a molten material with calcium silicate as the main component obtained when yellow phosphorus is produced by an electric furnace method. It is a powder material obtained by quenching and granulating and then grinding; zeolite powder is a powder material made by grinding natural clinoptilolite rock or mordenite rock.

[0026] Beneficial effects of the present invention:

[0027] Compared with the prior art, the composite roadbed filler made of recycled construction solid waste in the present invention organically combines two types of waste, construction solid waste and mineral admixture, giving full play to their respective advantages, solving the problems of high-quality recycling of solid waste and shortage of sand and gravel materials for highway construction. It can be applied to the fully recycled construction solid waste concrete prepared from prefabricated components in highway construction such as conical slopes, arched skeletons and side ditch paving, and can simultaneously improve the anti-seepage and anti-freeze properties. DETAILED DESCRIPTION

[0028] The parameters of the specific chemical substances used in the examples are from the following sources:

[0029] Nano-montmorillonite: 50nm, manufacturer is Tuoyi New Materials (Guangzhou) Co., Ltd., model is TY-710C.

[0030] Nano-silicon dioxide: 20nm, the manufacturer is Qinghe County Chaotai Metal Materials Co., Ltd., the brand is SF93.

[0031] Nano calcined kaolin: 50nm, manufacturer is Tuoyi New Materials (Guangzhou) Co., Ltd., model is TY-209.

[0032] Fly ash: The manufacturer is Wuhan Jiyesheng Chemical Co., Ltd., and the product number is A01085.

[0033] Slag powder: S95 grade slag powder.

[0034] Tannic acid: purity is 81%, molecular weight is 1701.2, extracted from gallnut, 95% passes 80 mesh, manufacturer is Shaanxi Haochen Biotechnology Co., Ltd.

[0035] Phase change wax: hot spot is 21±2℃, melting heat ≥190J / g, manufacturer is Nanyang Energy Chemical Co., Ltd. , model number is NYXC-21.

[0036] Water reducing agent: The manufacturer is Jiangsu Subote New Materials Co., Ltd., model is SBTJM®-VIII.

[0037] Example 1

[0038] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste and 3 parts by weight of fly ash.

[0039] The preparation method of the construction solid waste is as follows:

[0040] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0041] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification; the recycled coarse aggregate and the recycled fine aggregate are mixed to obtain the construction solid waste.

[0042] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0043] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste and 3 parts by weight of fly ash.

[0044] Example 2

[0045] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste and 3 parts by weight of slag powder.

[0046] The preparation method of the construction solid waste is as follows:

[0047] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0048] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification; the recycled coarse aggregate and the recycled fine aggregate are mixed to obtain the construction solid waste.

[0049] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0050] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste and 3 parts by weight of slag powder.

[0051] Example 3

[0052] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0053] The preparation method of the construction solid waste is as follows:

[0054] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0055] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification; the recycled coarse aggregate and the recycled fine aggregate are mixed to obtain the construction solid waste.

[0056] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0057] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0058] Example 4

[0059] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0060] The preparation method of the construction solid waste is as follows:

[0061] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0062] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification;

[0063] (3) 60 g of 8 wt% tannic acid aqueous solution and 40 g of 5 wt% gelatin aqueous solution were mixed, stirred at 5500 r / min for 30 minutes, dried, ground and sieved, and then added to 50 g of 50 wt% ethylene glycol aqueous solution for dilution to obtain a composite adhesive;

[0064] (4) 100 g of phase change wax and 50 g of nano-montmorillonite were mixed, and the mixture was stirred under a vacuum condition of 85 kPa for 7 hours until the adsorption was complete, thereby obtaining doped nano-montmorillonite;

[0065] (5) 700 g of recycled coarse aggregate, 150 g of composite binder, and 150 g of doped nano-montmorillonite were added to 1600 g of water, and stirred at a speed of 3000 r / min for 1.5 hours to allow the doped nano-montmorillonite to completely adhere to the surface of the recycled coarse aggregate for shaping, and dried to a moisture content of less than 2.0 wt %, and finally mixed with 300 g of recycled fine aggregate to obtain the construction solid waste.

[0066] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0067] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0068] Example 5

[0069] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0070] The preparation method of the construction solid waste is as follows:

[0071] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0072] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification;

[0073] (3) 60 g of 8 wt% tannic acid aqueous solution and 40 g of 5 wt% gelatin aqueous solution were mixed, stirred at 5500 r / min for 30 minutes, dried, ground and sieved, and then added to 50 g of 50 wt% ethylene glycol aqueous solution for dilution to obtain a composite adhesive;

[0074] (4) Mix 100 g of phase change wax and 50 g of nano-silicon dioxide, place under 85 kPa vacuum conditions and stir for 7 hours until adsorption is complete to obtain doped nano-montmorillonite;

[0075] (5) 700 g of recycled coarse aggregate, 150 g of composite binder, and 150 g of doped nano-montmorillonite were added to 1600 g of water, and stirred at a speed of 3000 r / min for 1.5 hours to allow the doped nano-montmorillonite to completely adhere to the surface of the recycled coarse aggregate for shaping, and dried to a moisture content of less than 2.0 wt %, and finally mixed with 300 g of recycled fine aggregate to obtain the construction solid waste.

[0076] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0077] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0078] Example 6

[0079] A construction solid waste recycled composite roadbed filler consists of 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0080] The preparation method of the construction solid waste is as follows:

[0081] (1) 1000 g of waste concrete is sent to a crusher for primary crushing, and then sent to a screening machine for screening to be divided into large-size solid waste with a particle size of 10-50 mm and small-size solid waste with a particle size of 1-10 mm;

[0082] (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The materials after secondary screening are sent to a washing machine for water washing, and 700 g of recycled coarse aggregate with a particle size of 5-30 mm and 300 g of recycled fine aggregate with a particle size of 1-5 mm are obtained by wind classification;

[0083] (3) 60 g of 8 wt% tannic acid aqueous solution and 40 g of 5 wt% gelatin aqueous solution were mixed, stirred at 5500 r / min for 30 minutes, dried, ground and sieved, and then added to 50 g of 50 wt% ethylene glycol aqueous solution for dilution to obtain a composite adhesive;

[0084] (4) 100 g of phase change wax and 50 g of nano calcined kaolin were mixed, and stirred under 85 kPa vacuum conditions for 7 hours until the adsorption was complete to obtain doped nano montmorillonite;

[0085] (5) 700 g of recycled coarse aggregate, 150 g of composite binder, and 150 g of doped nano-montmorillonite were added to 1600 g of water, and stirred at a speed of 3000 r / min for 1.5 hours to allow the doped nano-montmorillonite to completely adhere to the surface of the recycled coarse aggregate for shaping, and dried to a moisture content of less than 2.0 wt %, and finally mixed with 300 g of recycled fine aggregate to obtain the construction solid waste.

[0086] The preparation method of the construction solid waste recycled composite roadbed filler is as follows:

[0087] The construction solid waste recycled composite roadbed filler is obtained by mixing 7 parts by weight of construction solid waste, 2 parts by weight of fly ash and 1 part by weight of slag powder.

[0088] Application Examples 1-6

[0089] The specific preparation method of recycled concrete from construction solid waste is as follows:

[0090] 400 g of cement, 1000 g of the construction solid waste recycled composite roadbed filler of Example 1-6, and 5 g of a water reducing agent were added to 300 g of water and stirred at room temperature for 1 hour to obtain construction solid waste recycled concrete.

[0091] Test Example 1

[0092] Corresponding to use cases 1-4, the construction solid waste recycled concrete was tested for impermeability. The impermeability test was conducted in accordance with the relative permeability test in the industry standard SL / T 352-2020 "Test Procedure for Hydraulic Concrete". The standard test mold specified in the specification was used to prepare the test specimens. After the test specimens were formed and demolded, the cement slurry film on both ends of the test block was brushed off with a wire brush, and then cured in the curing room. After curing to the age, the test specimens were taken out and wiped clean. The water pressure of the impermeability tester was increased to 0.8MPa at a time, kept constant at this pressure for 24 hours, and then the pressure was reduced and stopped; when the concrete was relatively dense, the water pressure was changed to 1.2MPa, and the test was started after being kept constant at this pressure for 24 hours. Six test specimens were set in each group of embodiments, and their relative permeability coefficients were calculated and the average values ​​were summarized as shown in Table 1.

[0093] The relative permeability coefficient formula is as follows: K r =aD 2m / 2tH=7.66×10 -8 ×D 2 m

[0094] Where:

[0095] K r ——Relative permeability coefficient of concrete, cm / h;

[0096] D m ——water seepage height of the test piece, cm;

[0097] H——water pressure, expressed as water column height, cm, 1MPa water pressure expressed as water column height is 10200cm;

[0098] t——constant pressure time, h;

[0099] a——Water absorption rate of concrete, which can be taken as 0.03.

[0100] The average value of the six test pieces is taken as the test result (rounding interval 0.1×10 -8 cm / h).

[0101] Table 1 Results of anti-seepage performance test

[0102] Application Example 1 Application Example 2 Application Example 3 Application Example 4 Relative permeability coefficient (cm / h) <![CDATA[0.50×10 -8 ]]> <![CDATA[0.47×10 -8 ]]> <![CDATA[0.43×10 -8 ]]> <![CDATA[0.29×10 -8 ]]>

[0103] In Application Examples 1 and 2, the construction solid waste recycled composite roadbed filler is prepared by mixing the construction solid waste with fly ash or slag powder, while in Application Examples 3 and 4, the construction solid waste is mixed with fly ash and slag powder. It can be seen from the table that the impermeability of Application Examples 3-4 is better than that of Application Examples 1-2. One reason is that the synergistic effect of fly ash and slag powder improves the impermeability of concrete. The two can react secondary with substances such as calcium hydroxide produced by cement hydration to generate more gel substances, which fill the pores inside the concrete, make the structure more compact, and better improve the microstructure of the concrete, thereby improving its impermeability; the second reason is The particle size of fly ash and slag powder forms a particle size gradient with cement and construction solid waste. The particles fill each other, further reducing the gaps between fine aggregate particles, making them more compact, reducing the number and size of connected pores, and thus reducing the channels for water penetration; and Application Example 4, based on Application Example 3, adds composite adhesives and doped nano-montmorillonite to perform special treatment on the surface of recycled coarse aggregate during the preparation of construction solid waste. Different ingredients and treatment methods will affect the pore structure and density of the concrete, resulting in different relative permeability coefficients. Application Example 4 has the smallest relative permeability coefficient and the best water seepage resistance.

[0104] Test Example 2

[0105] The anti-chloride ion penetration performance test of the construction solid waste recycled concrete corresponding to Example 1-4 was carried out by using the dry-wet cycle method. Three groups of specimens were set for each application case. The specimen with a length, width and height of 100mm×100mm×200mm was placed with the top surface facing up in a 3.0wt% sodium chloride solution (30g of sodium chloride was weighed and dissolved in 970g of deionized water) with an immersion depth of 5cm. After immersion for 24 hours, it was taken out and air-dried. After 1 hour, it was placed in an oven and dried at 60℃ for 45 hours. After drying, it was taken out and cooled for 2 hours, and then immersed in the sodium chloride solution again with an immersion depth of 5cm. It took a total of 720 hours from the beginning of immersion to the end of drying. Then, concrete powder samples with a depth of 15cm were drilled from the longitudinal central axis of the two sides of the specimen in sections, and the soluble chloride ion content in the sample was analyzed by chemical titration method, as shown in Table 2.

[0106] Table 2 Chloride ion resistance test results

[0107] Application Example 1 Application Example 2 Application Example 3 Application Example 4 Chloride ion% 0.018 0.016 0.013 0.010

[0108] The construction solid waste recycled concrete added to the construction solid waste recycled composite roadbed filler in Application Examples 1-4 uses construction solid waste as the basic material, providing a basic skeleton structure and certain mechanical properties for the recycled concrete, wherein the pore structure and surface characteristics may have some factors that are not conducive to anti-seepage, and will provide channels for the penetration of chloride ions. Application Examples 1 and 2 respectively add fly ash and slag powder to act together with construction solid waste, Application Example 3 adds fly ash and slag powder to act together with construction solid waste, and Application Example 4 performs special treatment on construction solid waste based on Application Example 3. Chloride ions can diffuse through non-porous pathways such as microcracks and capillary channels inside concrete, among which fly ash makes it more compact and reduces pores; the active silica and alumina in fly ash can react with calcium hydroxide generated by cement hydration to form stable hydrated calcium silicate, thereby filling microcracks and pores in concrete and enhancing the compactness of concrete; slag powder and fly ash work together to make the internal structure of concrete denser. The synergistic effect of the two makes the chloride ion penetration resistance better than that of application example 1-2 when only fly ash or slag powder is added.

[0109] Test Example 3

[0110] The antifreeze performance test of construction solid waste recycled concrete corresponding to Example 3-6 was carried out. Five groups of specimens were set for each application case. The specimen size was 100mm×100mm×20mm in length, width and height. The specimen age was 30d. The test was carried out on the surface of the specimen by a freeze-thaw device. The amount of surface peeling of the specimen after freeze-thaw was measured to measure the surface antifreeze performance of the specimen. The test was based on the national standard GB / T 35723-2017 "Rapid Test Method for Surface Salt Freeze of Concrete Pavement Bricks for Antifreeze Performance". The number of peeling per unit area was calculated and the average value was summarized as shown in Table 3.

[0111] The calculation formula is as follows: N = m / A × 10 -6

[0112] Where:

[0113] N——The amount of peeling per unit area of ​​the sample, in grams per square meter (g / m 2 );

[0114] m——the total mass of the peelings from the test surface after 25 freeze-thaw cycles, in grams (g);

[0115] A——the area of ​​the test surface, in square millimeters (mm).

[0116] The test results are expressed as the arithmetic mean of 5 specimens and the maximum value of a single specimen.

[0117] Table 3 Test results of frost resistance performance

[0118] Application Example 3 Application Example 4 Application 5 Application 6 Amount of peeling per unit area <![CDATA[1.49 g / m 2 ]]> <![CDATA[1.40 g / m 2 ]]> <![CDATA[1.43 g / m 2 ]]> <![CDATA[1.44 g / m 2 ]]>

[0119] Application Example 3-4 effectively reduces the amount of spalling per unit area of ​​concrete through the combined action of slag powder and fly ash, and reduces the porosity of concrete so that deicing salt is not easy to enter and stay in the concrete, thereby improving the concrete's resistance to salt frost damage and reducing the amount of spalling per unit area of ​​concrete. Application Example 4, based on Application Example 3, performs special treatment on the surface of recycled coarse aggregate in the preparation process of construction solid waste. Application Example 4 uses a composite adhesive to adhere doped nano-montmorillonite to the surface of recycled coarse aggregate when preparing construction solid waste, making its shape smoother and flatter, and more uniform and compact in the application of concrete. The composite adhesive is made of tannic acid aqueous solution and gelatin aqueous solution. The composite adhesive has low-temperature weather resistance and still maintains adhesion in low-temperature environments, avoiding the problem of easy freezing and loss of viscosity in actual applications. Among them, ethylene glycol can effectively dilute and disperse the active ingredients in the adhesive, and help to improve the fluidity and adhesion properties of the adhesive; gelatin is a protein polymer containing a large number of polar amino acid residues, such as serine, aspartic acid, etc. These residues give gelatin good film-forming and gelling properties; tannic acid is a natural organic compound with multiple biological activities. It forms hydrogen bonds with the polar amino acid residues in silk protein through its rich hydroxyl groups to form adhesion, making the doped nano-montmorillonite and recycled coarse aggregate more firmly combined; at the same time, it can better resist the damage of external stress, reduce the spalling of the concrete surface, reduce the spalling amount per unit area, and improve the anti-freeze performance.

[0120] The nano-montmorillonite in Application Example 4 has a large specific surface area and good adsorption. After being treated with recycled coarse aggregate and applied to concrete, the adsorption of nano-montmorillonite can adsorb and combine the phase change material phase change wax under pressure. The phase change wax can buffer the stress concentration area caused by temperature change in the concrete to a certain extent during the phase change, making the stress distribution inside the concrete more uniform, thereby reducing the damage to the structure caused by stress concentration, cracks or shedding, etc., and improving its antifreeze performance. From the filling effect point of view, the doping of nano-montmorillonite makes it more fully in contact with the recycled coarse aggregate. After the combination of the two, the pores of different sizes originally existing in the concrete can be filled, making the concrete structure more compact; the compact structure effectively blocks the channel for water penetration and reduces the possibility of water entering the concrete during the freezing and thawing process. In terms of pore structure optimization, the combination of nano-montmorillonite and recycled coarse aggregate refines the spatial structure compared with the unshaped recycled coarse aggregate. The more uniform distribution can effectively reduce the migration speed of water in the concrete, further reducing the damage caused by water freezing and expansion to the concrete. The optimization of the pore structure, together with the effects of preventing water penetration and enhancing compactness, makes the concrete of this embodiment have better antifreeze performance in low temperature environment. Based on Application Example 4, Application Examples 5 and 6 respectively use nano-silicon dioxide and nano-calcined kaolin to replace nano-montmorillonite. Although the two also have high activity and a certain filling effect, the particle morphology and surface properties are not exactly the same. Although they can fill the internal pores of concrete to a certain extent and improve the microstructure of concrete, compared with nano-montmorillonite, its adsorption performance is relatively weak. When combined with phase change wax, it cannot effectively adsorb phase change wax like nano-montmorillonite and make it uniformly dispersed in the concrete system, resulting in the effect of resisting stress concentration caused by temperature changes. It is not as good as nano-montmorillonite, making the uniformity of stress distribution inside the concrete slightly worse. Therefore, the amount of spalling per unit area in Application Examples 5-6 in Test Example 3 is slightly higher than that in Application Example 4.

[0121] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A composite roadbed filler made of recycled construction solid waste, characterized by: The construction solid waste recycled composite roadbed filler is composed of construction solid waste and mineral admixtures; The construction solid waste and the mineral admixture are mixed in a mass ratio of 6-8:2-4; The mineral admixture is one or more of fly ash, silica ash, slag powder, limestone powder, phosphorus slag powder and zeolite powder; The preparation method of the construction solid waste is as follows, in parts by weight: (1) 80-120 parts of waste concrete are sent to a crusher for primary crushing, and then sent to a screening machine for screening to separate solid waste with large particle size and solid waste with small particle size; (2) The large-size solid waste and the small-size solid waste are respectively sent to a crusher for secondary crushing, and are respectively sent to a screening machine for screening. The secondary screened materials are sent to a washing machine for washing, and 40-110 parts of recycled coarse aggregate and 10-40 parts of recycled fine aggregate are obtained by wind classification; (3) Mix 5-7 parts of tannic acid aqueous solution and 3-5 parts of gelatin aqueous solution, stir at 5000-6000 r / min for 20-40 minutes, dry, grind and sieve, and add to 4-6 parts of ethylene glycol aqueous solution for dilution to obtain a composite adhesive; (4) Mix 8-12 parts of phase change wax and 4-6 parts of nano-montmorillonite, place under 80-90 kPa vacuum conditions and stir for 6-8 hours until adsorption is complete to obtain doped nano-montmorillonite; (5) Add 50-70 parts of recycled coarse aggregate, 10-20 parts of composite adhesive, and 10-20 parts of doped nano-montmorillonite to 100-150 parts of water, stir at a speed of 2000-4000 r / min for 1-2 hours to allow the doped nano-montmorillonite to completely adhere to the surface of the recycled coarse aggregate for shaping, dry until the moisture content is less than 2.0wt%, and finally mix with recycled fine aggregate to obtain the construction solid waste.

2. The construction solid waste recycled composite roadbed filler according to claim 1, characterized in that: The mineral admixture is a mixture of fly ash and slag powder.

3. The construction solid waste recycled composite roadbed filler as claimed in claim 2, characterized in that: The mineral admixture is a mixture of fly ash and slag powder in a mass ratio of 2-4:1-2.

4. The construction solid waste recycled composite roadbed filler according to claim 1, characterized in that: In the step (1), the large particle size is 10-50 mm, and the small particle size is 1-10 mm.

5. The construction solid waste recycled composite roadbed filler according to claim 1, characterized in that: In the step (1), the particle size of the recycled coarse aggregate is 5-30 mm, and the particle size of the recycled fine aggregate is 1-5 mm.

6. The construction solid waste recycled composite roadbed filler according to claim 1, characterized in that: The tannic acid aqueous solution in step (3) is a 5-10 wt % tannic acid aqueous solution.

7. The construction solid waste recycled composite roadbed filler as claimed in claim 1, characterized in that: The gelatin aqueous solution in step (3) is a 4-6 wt % gelatin aqueous solution.

8. The construction solid waste recycled composite roadbed filler as claimed in claim 1, characterized in that: The ethylene glycol aqueous solution in step (3) is a 40-60wt% ethylene glycol aqueous solution.

9. The method for preparing the composite roadbed filler from construction solid waste as claimed in any one of claims 1 to 8, characterized in that: The preparation method is as follows: The construction solid waste and mineral admixture are mixed to obtain the construction solid waste recycled composite roadbed filler.

Citation Information

Patent Citations

  • Building solid waste regenerated composite roadbed filler and preparation method thereof

    CN111393065A

  • Phase-change energy-storage composite material and preparation method thereof

    CN101121875A

  • Environmentally friendly phase change energy storage dry-mixed mortar and preparation method thereof

    CN106186873A

  • Energy-saving environment-friendly wall phase change thermal mortar and preparation method thereof

    CN106186946A

  • Multi-element matrix composite phase-change energy-storage material and preparation method thereof

    CN109837069A